Globalization India - Bhambhri, C. P. (Delhi, 2005)
This study is focused on the impact of imperialist globalization on the ideological and intellectual make up of Third World leaders of the ruling Classes, Nations and States. Imperialist globalization of the 1990s has impacted very powerfully on the thinking processes of the leaders of society and the state who have accepted their incapability to stand up against the pressures and dictations of the Supra-National capitalist institutions, Democracy, Nation and State are relevant even for the currently Globalized Twenty first Century. This study substantiates the argument that Global dictations can be resisted by domestic Nation- States of the Third World including India if popular classes are mobilized for democratic struggles against imperialist globalization and 'hyper-power' imperialist America. US$ 30 Table of Contents : Acknowledgments 1. Imperialism-led Globalization: A Perspective 2. Assertion of National Sovereignty to Compradorism 3. New Global Capitalism and Democratic State 4. Globalization, Market and State 5. Central Government in the Age of New Globalization: New Directions of Indian Federalism 6. Globalization and Neo-Primordialism 7. New Global Imperialism and the Idea of Nation 8. Global Capitalism and Peripheral Capitalist Democratic Nation-State Systems 9. Legitimacy and Accountability of State Systems: New Challenges 10. Political Economy of the Indian State: 1991-1996 11. Political Economy: Pluses and Minuses 12. New Economic Policy: Indian State and Bureaucracy 13. Globalization, Liberalization and Welfare State 14. Globalization, Liberalization and Institutions for Governance in India 15. Journey from Intervention to Liberalization 16. Grappling with Globalization 17. Federalism
Keywords: Globalisation